2014
DOI: 10.2131/jts.39.803
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidins inhibit H<sub>2</sub>O<sub>2</sub>-induced osteoblastic MC3T3-E1 cell apoptosis via ameliorating H<sub>2</sub>O<sub>2</sub>-induced mitochondrial dysfunction

Abstract: -Oxidative stress represents a major cause of cellular damage and death in pathological conditions including osteoporosis, in which oxidative stress is associated with increased bone resorption and low bone mass. And grape seed proanthocyanidins are a group of polyphenolic bioflavonoids which are known to possess broad pharmacological activity and therapeutic potential, exerting a protective role against oxidant injury. The aim of our study was to investigate whether proanthocyanidins exert an anti-apoptosis e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 44 publications
(53 reference statements)
6
26
0
Order By: Relevance
“…In the oxidative stress model we used, we clearly found that the mitochondrial membrane potential and respiratory chain complex activity were significantly reduced in conditions where production of mitochondrial ROS was significantly up-regulated. This result is consistent with that from a previous study using MC3T3-E1 osteoblasts, where complex IV activity was reduced [32]. Furthermore, to determine whether mitochondrial fission is required for activation-induced ROS generation in osteoblasts, we examined the effect of Drp1 inhibition using a pharmacological Drp1 inhibitor (mdivi-1).…”
Section: Discussionsupporting
confidence: 89%
“…In the oxidative stress model we used, we clearly found that the mitochondrial membrane potential and respiratory chain complex activity were significantly reduced in conditions where production of mitochondrial ROS was significantly up-regulated. This result is consistent with that from a previous study using MC3T3-E1 osteoblasts, where complex IV activity was reduced [32]. Furthermore, to determine whether mitochondrial fission is required for activation-induced ROS generation in osteoblasts, we examined the effect of Drp1 inhibition using a pharmacological Drp1 inhibitor (mdivi-1).…”
Section: Discussionsupporting
confidence: 89%
“…A recent study showed that proanthocyanidins could ameliorate H 2 O 2 -induced mitochondrial dysfunction by promoting mitochondrial respiratory chain complex IV and reducing the levels of mitochondrial superoxide 16 . Moreover, grape seed extract can reduce silica-induced and bleomycin-induced pulmonary fibrosis in rats 17 , and GSPs protect mice from RILI by inhibiting the TGF-β1/Smad3/Snail signaling pathway, scavenging hydroxyl radicals (•OH) and modulating the levels of RILI-associated cytokine (interferon-γ, IL-4 and IL-13) derived from Th1/Th2 cells 18 .…”
Section: Introductionmentioning
confidence: 99%
“…These results partly explained the underlying mechanisms for the SDSS effects on ROS scavenging. Mitochondrial dysfunction is also an important target and source of ROS, and is characterized by an increase in membrane permeability, which caused release of cytochrome c. Mitochondrial dysfunction participates in aging-related disease, including osteoporosis (Zhang et al, 2014; Lane et al, 2015). Our data show that cytosolic cytochrome c accumulation induced by H 2 O 2 was significantly alleviated after pretreatment with SDSS.…”
Section: Discussionmentioning
confidence: 99%